Environmental impact of the Brazilian agrarian reform process from 1985 to 2001 - Steeg, Jeannette van de; Sparovek, G.; Ranieri, S.B.L.; Maule, R.F.; Cooper, M.; Neto, D.D.; Alves, M.C. (FapUNIFESP, 2006)
During the past 20 years, most settlements of the Brazilian Agrarian Reform (AR) have been established in or near better-preserved natural ecosystems, where environmental impact is likely to be negative and contribute to natural resources degradation. The objective of this work is providing a first, comprehensive insight of the impacts related to the environmental quality of these settlements, based on the primary survey of 4,340 AR settlements installed between 1985 and 2001. An index was calculated to integrate different aspects of environmental impacts in one single number. The index showed significant regional variation, with lower values (low environmental quality) for the North and Northeast of Brazil, intermediate values for the Central-west and Southeast, and high values for the South. Environmental impacts resulting from AR and settlement creation are slowly decreasing with time, but are still very high in absolute values. The lack of protection of riparian areas, cultivation of legal reserves, and deforestation, are the main concerns related to environmental impacts.